Respuesta :

Given Equations :

❤  -x + y = 4 --------------- [1]

❤  3x - 4y = -13 -------------- [2]

Now Consider Equation [1]

⇒ -x + y = 4

⇒ y = x + 4

Substitute y = x + 4 in Equation [2]

⇒ 3x - 4(x + 4) = - 13

⇒ 3x - 4x - 16 = -13

⇒ -x = 16 - 13

⇒ x = -3

Substituting x = -3 in Equation [1], We get :

⇒ 3 + y = 4

⇒ y = 1

⇒ (x , y) = (-3 , 1)

Option (b) is the Answer

therefore from the pictures attached to this answer (x, y)=(-3, 1)
Ver imagen ciscodahchamp
Ver imagen ciscodahchamp